Communio - wspólnota zakonna - wzajemne powiązanie instytucji - Śliwa, Jan (Prawo Kanoniczne, 1998)
In his article the author presents: 1) Introduction. 2) The meaning of the notion „communio”. 3) The religious community as reflecting „communio”. 4) Practical postulates. The aim of the article is to point out the correlation between the notions „communio” and community. It is the author’s conviction that the religious community is a representation in reality and in legal institutions of the theological content of the notion „communio”.